Development of the Chinese giant salamander Andrias davidianus farming industry in Shaanxi Province, China: conservation threats and opportunities. Issue 2 (11th March 2015) - Cunningham, Andrew A.; Turvey, Samuel T.; Zhou, Feng; Meredith, Helen M. R.; Guan, Wei; Liu, Xinglian; Sun, Changming; Wang, Zhongqian; Wu, Minyao
Abstract: The Chinese giant salamander Andrias davidianus is endemic to China and is Critically Endangered, largely because of overexploitation for food. This species is an expensive delicacy in China, and a rapidly growing industry to farm the species has developed throughout much of the country, centred on the Qinling Mountain region of Shaanxi Province. During a 2010 workshop on Chinese giant salamander conservation, which involved a range of stakeholders from across China, it became clear that the conservation community knew little about the salamander farming industry and whether it posed actual or potential threats or opportunities for conservation of the Chinese giant salamander. We therefore conducted a series of investigations to understand the industry better. Our results indicate that although farming of Chinese giant salamanders has the potential to be a positive development for conservation by supplying market demand with farmed animals, it is currently more likely to threaten than support conservation of the species, with continued overexploitation and the potential added impacts of infectious disease and genetic pollution arising from farming practices such as movement of animals across the country and the release of untreated farm wastewater and farmed salamanders to the wild.